"No End or Return": Thematics of Impasse. (2nd January 2016) - Méndez, Teresa
ABSTRACT: This article explores therapeutic impasse through the dual lens of relational theory and infant research. Particular attention is paid to the role that enactment, rupture and repair, and nonverbal communication play in impasse dynamics. Defined broadly—as any time a therapist and patient feel stuck—impasse is conceptualized as an expectable, even inevitable, component of the treatment relationship. The implications for navigating impasses are considered through a clinical vignette developed as a case composite to ensure confidentiality.